Interaction of calcium with negative lipids in planar bilayer membranes. Influence of the solvent. - Laclette, J P (1977)
The interaction of Ca++ with acidic phospholipids in black lipid films and lipid bilayers formed from two monolayers was studied by measuring their physical stability and conductance. It was found that the addition of CaCl2 to only one side of lipid bilayers formed from phosphatidylserine or cardiolipin does not appreciably change these parameters. In contrast, black films are unstable to the asymmetric addition of CaCl2. Therefore, the destabilizing effect of Ca++ cannot be attributed to a surface charge difference. The only variation in composition between both bilayer membranes, namely the solvent content of the bilayer, seems to be responsible for the distinctive effect of Ca++. A tentative explanation is presented.